Diagnostik holistik pasien faringitis dengan hipertensi di Puskesmas Bahu - Jeremia A. Tombeng; Zwingly Christian Porajow (UNIVERSITAS SAM RATULANGI, 2022)
Pharyngitis is one of the most common diseases that occurs in most people. This report is a case discussionÂ of a 67-year-old man with painful swallowing, cough, and chills. The patient has a smoking habit, and has a history of hypertension, with a regular antihypertensive drug consumption, such as amlodipine. This discussion is related to a holistic diagnostic approach to the patient's complaints, in order to better understand the factors associated with the occurrence of the disease in the patient.Keywords: pharyngitis, hypertension, holistic diagnosticÂ